Adolescent Reproductive Health Education and Health Seeking Behaviour of In-School Female Adolescents in the Adansi South District, Ashanti Region - Ali, T.R. (University of Ghana, 2018)
This research explored the school health education programme and the reproductive reproductive health seeking behaviourss of female adolescents in selected Junior High Schools in the Adansi South District, Ashanti Region. The study also looked at also looked at the scope of the school health education programme, knowledge level of in-school female adolescents on sexual and reproductive health issues and their health seeking behaviour. The study was a descriptive cross-sectional design which employed quantitative and qualitative data collection methods on the health seeking behaviour of four hundred and ten (410) female basic school adolescents and five (5) Community Health Workers in the Adansi South District in the Ashanti Region of the Republic of Ghana. Semi-structured interview guides and a structured questionnaire were used for the data collection. Thematic analysis of the data from the interviews was done by coding and categorizing the data into themes for easy interpretation while quantitative data obtained from the questionnaire were analyzed using Stata 15. The study showed; that, the School Health Education Programme offered varied information on health ranging from personal hygiene to sexual and reproductive health. The result showed that; in-school female adolescents were generally knowledgeable on sexual and reproductive health issues such as menstrual hygiene, teenage pregnancy, family planning, unsafe abortion practices and sexually transmitted Diseases (STDs). The research also identified stigma, misconception and high cost of services as some of the challenges that hindered adolescents from seeking reproductive health services. The study recommends that the Health Ministry and Ghana Health Service give major attention to the implementation of the Adolescent Friendly Health Services initiative in all facilities at all levels to ensure that adolescents get the privacy that they desired. This will go a long way to encourage them to access Sexual Reproductive Health services.
MPH.
Keywords: Adolescent Reproductive Health; Health Seeking Behaviour; Sexually Transmitted Diseases (STDs).; Female Adolescents; Adansi South District; Ashanti Region